Multiplex PCR for detection of three exfoliative toxin serotype genes in Staphylococcus aureus - Růzicková, V; Voller, J; Pantůcek, R; Petrás, P; Doskar, J (Folia microbiologica, 2005)
Rapid and specific detection of exfoliative toxin (ET)-producing Staphylococcus aureus strains by multiplex polymerase chain reaction (PCR) was used for identification of exfoliative toxin genes in a diverse set of 115 clinical S. aureus strains isolated in 14 Czech cities between 1998 and 2004. Fifty-nine wild-type ET-positive isolates of which 40 strains were the causative agents of toxic epidermolysis in neonates were classified into 4 PCR types. The genes coding for ETA, ETB or ETD were not detected in any of non-ET-producing isolates. The PCR method using the multiplex and specific primer set was shown to be reliable in rapid identification of the exfoliative toxin producing S. aureus and can be used as a convenient tool for hospital epidermolytic infection control.
Keywords: exfoliatiny; polymerázová řetězová reakce; Staphylococcus aureus; Česká republika; stafylokokové infekce kůže; Adult; dospělí; Czech Republic; novorozenec; DNA, Bacterial; DNA bakterií; lidé; ženské pohlaví; Humans; Serotyping; Infant, Newborn; sérotypizace; Polymerase Chain Reaction; Exfoliatins; Female; Staphylococcal Skin Infections